Impact of post-conflict development interventions on maternal healthcare utilization - Muhammad Badiuzzaman; Syed Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We evaluate the effectiveness of a post-conflict development programme on maternal health-care utilization in the Chittagong Hill Tracts of Bangladesh. Our work varies from conventional impact evaluation studies because of the inclusion of two post-conflict psychosocial risks: the household's actual experience of violence, and subjective perceptions about violence, as key determinants of programme effectiveness. Following the difference-indifference estimator, and propensity score matching method this study establishes that the postconflict development programme undertaken by Chittagong Hill Tracts Development Facility of the United Nations Development Programme is successful in improving maternal health-care utilization. Despite this, forced settlement by outsiders, household experiences of conflict, and perceptions of insecurity lower maternal health-care utilization. The effectiveness of the programme would have been greater in the absence of conflict, although the programme may have mitigated some experiences of past conflict. The intervention fails to significantly narrow the inter-ethnic gap in terms of health-care utilization, chiefly attributable to the adverse effects of the forced settlement of non-indigenous peoples in the region.
Keywords: D74; I14; I15; 330; conflict; post-conflict reconstruction; healthcare usage; health inequality